Public Revenues and Expenditures in Kosovo (European Journal of Marketing and Economics, 2018)
Within this Thesis, efforts have been made to explore, analyse and address the role and importance of Public Revenues and Expenditures, regarding their functioning in the country, with particular emphasis on the Republic of Kosovo during 1999 - 2018. Following the end of the war in June 1999, the Republic of Kosovo faced serious challenges, which it should have gone through. After the war, between 1999 and 2008, Kosovo was administered by UNMIK. With the declaration of independence in 2008, the Republic of Kosovo assumed all the responsibilities in the management of public finances, where state activities related to the collection of public revenues and public expenditure coverage are steered and managed by the Ministry of Finance within the State Government. According to the Legislation of the Republic of Kosovo, accountability in the management of public money consists of a chain of participants, each of which is responsible for achieving certain goals, and each is accountable to the highest level authority for achieving these goals. The highest authority in this hierarchy is held by citizens, who are represented by elected members of the Assembly and Municipal governments. The Government elected by the Assembly then assigns responsibilities to the Ministers, in order to enforce government policies, who within the scope permitted by applicable rules, through regulations, policies and administrative arrangements, assign further powers and responsibilities to the senior managers of budget organizations and other users of public property. The research question put forward is: How will the Government, through public revenues and public expenditures with a budget management, impact the growth of goods, public services for the citizens of Kosovo.
Keywords: Public Revenues, Public Expenditures, Budget, Accountability